Penguasaan Bahasa Inggris Melalui Extensive Reading Program - Munjin Munjin (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
Even though there is no representative data reporting the profile of Indonesian studentsâ€™ proficiency in English, it seems that English teaching program has been largely unsuccessful. Factually, most of high school graduates just had average reading vocabulary of 1000 words, a number considered too small. This phenomenon needs an appropriate solution. Extensive Reading Program (ERP) may be the answer. Why? Because it can, with â€œeasy and interestingâ€ strategy, motivate studentsâ€™ interest in reading, increase their language acquisition, and eliminate their negative predisposition on English as either difficult language or bored lesson.